Blind test evaluation of accuracy in the identification and quantification of digestion corrosion damage on leporid bones - Lloveras, Lluís; Moreno-García, Marta; Nadal, Jordi; Thomas, Richard (Quaternary international, 2014)
The recording of digestion corrosion damage on the surface of archaeological skeletal remains is an important variable to take into account in taphonomic analyses. Different kinds of predators produce digestion damage of variable intensity. Consequently, digestion is one of the most distinctive features used to identify the agents of accumulation, alongside anatomical representation profiles and bone breakage patterns. In order to quantify digestion corrosion on taphonomic studies of leporid (rabbits and hares) remains, different categories of digestion, distinguishing five grades of intensity, have been proposed. However, as they are based on morphological characters and represent the division of continuous variation into qualitative ordinal categories, their evaluation is subject to inter-observer error. With the aim of quantitatively evaluating the magnitude of ambiguity in the identification of digestion surface modification, a blind test was conducted with 25 volunteers. Results show that absent and slight digestion damage was the easiest to categorise. The accuracy of grading intermediate and more advanced cases of digestion damage proved harder to separate. It is concluded that this system remains a reliable method for identifying the agents of leporid accumulation in the archaeological record. However, training in the identification of the effects of digestion damage is essential to obtain reliable scoring results.